BreastSurgANZ members recommendations for adjuvant systemic treatment and patient compliance in Australian breast cancer patients. Issue 11 (3rd September 2021) - Chan, Arlene; O'Neil, Nicola; Lomma, Chris; Chih, HuiJun; Willsher, Peter
Abstract: Background: We aimed to identify compliance with systemic treatment recommendations in early breast cancer (EBC) patients managed by Australian BreastSurgANZ members. Methods: A retrospective analysis of patients diagnosed with EBC included in BreastSurgANZ prospective database from January 2002 to December 2016 was conducted. Data was available on patients with BC treated by over 350 surgeons across the six states and two territories of Australia. Results: Over the 15 year period, 102 660 EBC episodes were recorded in 99 800 patients. As a group, the five key performance indicators (KPIs) set by the BreastSurgANZ relating to systemic treatment were achieved. Overall, patients were compliant with systemic treatment recommendations with 89.1% of patients receiving treatment in accordance with recommendations from their treating surgeon. The highest rate of non‐compliance with systemic treatment was for endocrine therapy (11.9%). Of the 2368 patients who did not proceed with the recommended endocrine treatment, 1284 (54%) patients did so because of patient refusal. Failure to receive chemotherapy was associated with older age (aOR 1.02; p < 0.001), patients living in regional areas (aOR 1.23; p = 0.001) and those with node negative disease (aOR 0.97; p = 0.003). Conclusions: The majority of Australian patients with EBC are being recommended for adjuvant systemic therapy in accordance with BreastSurgANZ KPI's. Treatment compliance was very high. This finding emphasises the importance of prospective data collection and auditing of established KPIs by surgeons, in areas other than direct surgical outcomes. Further research into the reasons why patients refuse treatment is needed. Abstract : Associations between patient characteristics and chemotherapy refusal, with adjusted † odds ratio (aOR) and 95% CI.